Conversor boost de três níveis: operação, modelagem e controle - Macêdo, Anne Karoline Pontes de (2022)
The multilevel DC-DC voltage step-up converter combines the conventional boost converter with the function of a switched capacitor, producing an output formed by several capacitors in series with self-balanced voltage and the same value. This feature is important for applications both in the case where the power supply of the converter is of low value (automotive sources, renewable energy systems, for example), as in the case where it supplies a multilevel inverter with balance problems in its multiple supply voltages (inverter with clamped diode, NPC, for example). In this work, both the full order and the medium reduced order models are developed for the configuration of a three-level voltage-boosting DC-DC converter, with two self-regulated output voltages of the same value. Through the technique of the switched signal flow diagram, models developed for large and small signals and for steady state are obtained. These diagrams allow the calculation of transfer functions that relate any of the converter variables. The effects of the voltage step-up inductor resistance were taken into account in the converter’s operation and, consequently, in its various transfer functions. In the traditional method, a cascade voltage and current controller is designed from the open-loop converter output transfer function. In contrast, this work combined, in a single signal flow diagram, the DC-DC converter and a controller based on state feedback. This allowed us to obtain a closed-loop transfer function directly from the switched signal flow diagram. The results obtained by simulating the transfer function are in accordance with the projected values and confirm not only the adequacy of the choice of principles considered, but also the good performance of the models developed. For validation purposes, the results were compared with the results obtained through SIMULINK. Due to the possibility of application of the studied converter, it is suggested a way forward for the probable modeling of the combination of a three-level step-up converter with the three-level NPC inverter.